Evaluating Native germplasm for extensive green roof systems for semiarid regions - Cáceres, Natalia; Imhof, Lelia; Suárez, Mario; Hick, Emmanuel; Galetto, Leonardo (Ornamental Horticulture, 2018)
Extensive green roofs (EGR) spaces constitute harsh and stressful growing environments, and consequently a limited range of plants species that can be routinely used there. The habitat template hypothesis suggests that EGR can be analogous as natural environments, what makes native plants as an alternative for these conditions. This paper aimed to assess the potential use of 15 native plants from Córdoba Province (Argentina) for green roofs, based on cover ability, survived rates and health status observations during a period of 414 days. Sedum acre L. was used as the control. Glandularia x hybrid, Phyla nodiflora (L.) Greene, Melica macra Nees, Eustachys retusa (Lag.) Kunth and Grindelia cabrerae Ariza kept up a 60% of coverage during all the period of study. The first two species had an outperformed green coverage (at 72th day; 95% and 98% respectively) in relation to the control species (Sedum acre; 87%). Eustachys retusa and Grindelia cabrerae grew progressively and kept their coverage constant proximally to 65%. Sedum acre, Grindelia cabrerae, Hysterionica jasionoides Willd, Melica macra, Phyla nodiflora, stood out in plant survival rates; but S. acre suffered changes in health status throughout the evaluation period, especially with low temperatures or at high humidity conditions. It is necessary to underline the reseeding potential of Eustachys retusa, a process that could guarantee perpetuation of the species on EGR.